(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Pregnancy is a state which requires more metabolic fuels. Changes in the hormonal levels in pregnancy alter lipid profile also in pregnant women. Thyroid hormone abnormality without any history of thyroid disease may lead to alteration of triglycerides, phospholipids, total cholesterol, and various lipoproteins levels in pregnancy which increases the risk for CVS disease. Aim: The aim of the study is to find out the association among TSH and lipid profile in pregnant females. Materials and Methods: The observational study was conducted at Biochemistry Department, SBKS Medical Institute & Research Center, Piparia, Vadodara, Gujarat, India. 100 antenatal cases from were enrolled after taking an informed consent. 50 pregnant women were in 2nd trimester and 50 pregnant women were in 3rd trimester. Blood samples were drawn to estimate lipid profile and TSH. Interpretation of data was done using Medcalc software. Results: The mean level of TSH was 1.71(1.26) in 2nd trimester pregnant females and 2.68(0.72) in 3rd trimester pregnant females, difference between them was statistically significant. Significant negative correlation was found between TSH and total cholesterol in 3rd trimester pregnancy. There was a significant positive correlation was seen between TSH and triglyceride and between TSH and VLDL in 3rd trimester. Conclusion: Significant increase in TSH level is found in 3rd trimester pregnant females compare to 2nd trimester pregnant females. Significant correlation is also found between TSH and lipid profile in 3rd trimester. Regular checkups of Thyroid hormones are required in later stages of pregnancy to prevent further complications.